Novel ultrastructural features of the nucleus of the ancestral dinoflagellate Oxyrrhis marina as revealed by freeze substitution fixation and volume electron microscopy - Fukuda, Yasuhiro; Suzaki, Toshinobu; Murata, Kazuyoshi; Song, Chihong (Frontiers in Protistology, 2025)
IntroductionOxyrrhis marina is thought to have diverged from other dinoflagellates at an early stage of their evolution and is considered to show their ancestral form. As for other current dinoflagellates, the species possesses condensed chromosomes throughout the cell cycle but shows some important differences. The chromosomes of O. marina are thinner and longer than those of other dinoflagellate species and do not show the repeating arch-shaped liquid-crystal structure that is found in core dinoflagellates. These morphological features were described originally about half a century ago from cells fixed using conventional chemical methods, which are prone to producing morphological artifacts. Therefore, it is crucial to reevaluate ultrastructural features using cells fixed by other methods.MethodIn this study, O. marina was fixed with freeze-substitution, a method that is less prone to artifacts in electron microscopy, in addition to conventional chemical fixation, and the details of chromosome structure were reexamined using volume electron microscopy.ResultsIn the four cells observed, the number of chromosomes was consistently nearly 400. The nucleus of O. marina has a single nucleolus at its center, to which, as in other dinoflagellates, multiple chromosomes are attached. Several nucleofilaments were observed penetrating the nucleolus. On the other hand, filamentous structures have been observed in chemically fixed chromosomes, but no such structures were observed in cells fixed by freeze-substitution. Tomographic analysis using volume electron microscopy confirmed the absence of these structural features.DiscussionThe number of chromosomes of O. marina was previously considered to be approximately 50, but this is only one-eighth of the number found in the present study (400). It is concluded that the chromosomes of O. marina are composed of tightly condensed and densely folded nucleofilaments, which are difficult to distinguish. This study revealed novel ultrastructural features in the chromosome of O. marina. These findings will help consider the evolutionary scenario through which the enigmatic dinoflagellate nucleus (dinokaryon) was established. In addition, this study indicated freeze-substitution fixation and volume electron microscopy would become a critical technique in elucidating the dinokaryon chromosome structure.